The structural development of zeolite-templated carbon under pyrolysis - Song, X. H. (2013)
Three activated carbon samples were synthesized via the pyrolysis of furfuryl alcohol (FA) impregnated in the porous framework of zeolite Y. The pyrolysis temperature was set at 900, 1050, and 1150 °C, respectively, to investigate its role on structural development. The surface properties of the carbon samples were characterized using XRD, SEM, Raman, and gas adsorption technologies. It is found that a low pyrolysis temperature is in favor of the structural regularity and the formation of small micropores (d < 1.0 nm), while a high temperature is necessary for the surface area/pore enhancement. However, a too high temperature will result in the collapse of micropores and the formation of mesopores.